2015
DOI: 10.4028/www.scientific.net/msf.814.574
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Silicon Carbide Reticulated Porous Ceramics by Organic Foam Impregnation

Abstract: Silicon carbide (SiC) reticulated porous ceramics were prepared by organic foam impregnation, using polyurethane sponges as template and deionized water or alcohol as slurry solvent. The sintering behavior, microstructures and apparent density of struct of the SiC reticulated porous ceramics fabricated using the aqueous slurry under different sintering aids and sintering process and the alcohol slurry were investigated comparatively. The experimental results showed that both the microstructures and apparent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…The test results demonstrated that the apparent density and microstructure of the samples produced with Y 2 O 3 + AlN as a sintering aid were superior to those formed with Al 2 O 3 as a sintering aid. The samples generated using alcohol slurry provided optimal properties for the aqueous slurry [36].…”
Section: Replica Techniquementioning
confidence: 99%
“…The test results demonstrated that the apparent density and microstructure of the samples produced with Y 2 O 3 + AlN as a sintering aid were superior to those formed with Al 2 O 3 as a sintering aid. The samples generated using alcohol slurry provided optimal properties for the aqueous slurry [36].…”
Section: Replica Techniquementioning
confidence: 99%
“…Finally, porous ceramics with good porosity can be obtained without adding additives. Compared with other material or process (adding pore-forming agent process [13], organic foam impregnation process [14], sol-gel process [15], freeze-drying process [16]), the pore size of porous ceramics synthesized from desert sand (from several microns to hundreds of microns) is much larger than these methods (smaller than tens of microns), which has advantages such as abundant raw materials, simple process route, adjustable porosity and good mechanical properties and can greatly reduce the synthesis cost and is suitable for low-cost and sustainable production of porous ceramics.…”
Section: Introductionmentioning
confidence: 99%